Is the Jason-2 DORIS oscillator also affected by the South Atlantic Anomaly?. Issue 12 (15th December 2016) - Willis, Pascal; Heflin, Michael B.; Haines, Bruce J.; Bar-Sever, Yoaz E.; Bertiger, Willy I.; Mandea, Mioara
Abstract: We analyzed time series of daily DORIS and GPS station coordinate estimates derived from Precise Point Positioning (PPP). The DORIS coordinates were estimated using Jason-2 precise orbits based on GPS data only, implying that the station positions from the two techniques are expressed in the same GPS-based terrestrial reference frame. Comparisons of 3-D vectors of such co-located stations show systematic biases in position around South America when compared to local geodetic ties. We conclude that these results could be explained by a sensitivity of the Jason-2/DORIS oscillator to radiation when the satellite passes over the South Atlantic Anomaly (SAA). The effect for Jason-2 manifests mainly as an offset in station coordinates, though there is also evidence of a drift at the start of the mission that diminishes in time. This contrasts with the experience on Jason-1, wherein large, persistent drifts were observed for stations in this same (SAA) region. The spurious drift is much (∼90%) smaller for Jason-2, which may be attributable to the steps taken prior to launch to harden the oscillator. Analysis of DORIS Doppler residuals may indicate some small degradation after 2009 for these stations.